From animal spirits to scientific revolution in Medicine (first part) (2018)
Introduction: Back in the sixth century BC, as part of the evolution of Medicine, a philosophical idea was proposed to explain how the nervous system works based on elements known as animal spirits, considered for many centuries as transmitters of sensation and movement. This philosophical concept, with a speculative basis, prevailed until the seventeenth century with subtle changes, but was later outweighed by demonstrative advances in neurophysiology.Discussion: Dogmatic tradition dictated for centuries that the animal spirits that controlled body actions were transmitted through the nerves; however, with the scientific revolution, such ideas were changed by better elaborated concepts supported by the scientific method.Conclusion: The old concept of the functioning of the nervous system changed radically after the seventeenth century, when knowledge on morphophysiological characteristics of the nerves was expanded, opening new doors in search of more coherent explanations detached from any religious influence.